Peran Teknologi (Media Sosial) Terhadap UMKM yang Dapat Meningkatkan Pembangunan Ekonomi - Andini Fadhila Hsb; Juwita Nur Pramita; Nur Anisah Hrp; Sinta Nova (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
Micro, small and medium enterprises (MSMEs) are the focus of this study, which seeks to examine how technological advances can increase their competitiveness and contribute to overall economic growth. This study found that MSMEs can benefit from e-commerce, social media, and financial technology, as well as other forms of technology, by reviewing the literature and conducting case studies. The results show that with the right innovation, operational efficiency, market expansion and access to capital can be significantly improved. However, there are a number of obstacles to technology adoption that this study highlights for MSMEs, including inadequate digital infrastructure and a lack of digital skills.